Faktor Yang Mempengaruhi Terjadinya Kekurangan Energi Kronik Pada Ibu Hamil - Endah Mulyani; Luluk Yuliati Yuliati; Diani Octaviyanti Handajani; Diska Winda Putri; Finnariqotul Aisiyah; Dwi Lindasari (STIKes Surya Global Yogyakarta, 2021)
ABSTRACTBackground of StudyChronic Energy Deficiency is a state of malnutrition in which the mother experiences a prolonged lack of food. Pregnant women are a nutritionally vulnerable group because maternal intake during pregnancy greatly affects the growth and development of the fetus. The problem of Chronic Energy Deficiency in pregnant women is an indirect cause of maternal death because Chronic Energy Deficiency increases the occurrence of complications of pregnancy and childbirth . This study aims to examine the effect of maternal characteristics (age, parity, education and occupation), family income, consumption patterns and body mass index before pregnancy on the incidence of Chronic Energy Deficiency in pregnant women.Methods : This study uses an analytic type with a cross sectional approach. The sample of this study was 54 pregnant women in Leran village, Manyar district, Gresik regency used multiple logistic regression.Results : Based on bivariate anlysis, level education variable (p=0.023), level of maternal knowledge (p=0.012), family income variable (p=0.036), consumption pattern variable (p=0.003) and maternal BMI before pregnancy variable (p=0.003) were associated to the incidence of Chronic Energy Deficiency on pregnant women in Leran village, Manyar district, Gresik regencyConclusion : Chronic Energy Deficiency in pregnant women is caused by various factors so that the steps that can be taken are to provide assistance as an effort to deal with the condition of pregnant womenKeywords : Chronic Energy Deficiency, Malnutrition, Pregnant Women